(untitled) (Revista Contexto & Educação, 2023)
This article presents the results of qualitative research, developed with a group of teachers participating in the extension program ‘Formative Cycles in Science and Mathematics Teaching’, which has a guiding question: how are teachers knowledge mobilized and transformed during the involvement of teachers in Modeling in Science and Mathematics (MCM) activities. For the constitution of the empirical data, we used the diaries referring to the continuing education meetings of six Mathematics teachers and the planning diaries of MCM activities. The analysis of the material follows the procedures of Textual Discursive Analysis, through which, we recognize the emergence of three categories: 1) evaluations on the MCM process, which denote the absence of knowledge of professional training compared to knowledge of the modeling process and the transformation of this knowledge throughout training; 2) doing MCM, in which there is a predominance of disciplinary knowledge and the understanding that the modeling process enables interdisciplinary relationships; 3) the transition to the classroom, in which the amalgamation of the different knowledge that constitutes the teaching profession is highlighted. We indicate that the categories textualize elements that denote marks of professional development of teachers in training.